Kemampuan Tanaman Hias Bunga Impatiens balsamina L. dan Mirabilis jalapa L. dalam Fitoremediasi Tanah Tercemar Logam Kadmium (Cd) - Juhriah Juhriah; Nur Fadila La Ganirun; Elis Tambaru (Universitas Hasanuddin, 2023)
This study aims to determine the content of cadmium (Cd) in contaminated soil at the Tamangapa Antang Final Disposal Site (FDS), Makassar and to know the content of 2 types of ornamental plants in accumulating heavy metal cadmium (Cd). The research was conducted by analyzing the content of the cadmium (Cd) in polluted soil taken from the FDS Tamangapa Antang landfill, Makassar. The soil was used as a planting medium for 2 types of ornamental plants in a planter bag consisting of 3 plants for each type of ornamental plant. Observation of the growth of plant species was carried out for 12 weeks. The observed parameters consist of plant height, stem diameter, number of leaves, length and width of leaves, biomass, metal removal and metal absorption efficiency. The results showed that the content of the cadmium (Cd) for the initial analysis of landfill soil had exceeded the park limit value of 0.53 μg/g. After using phytoremediation using Impatiens balsamina L. and Mirabilis jalapa L., both types of plants showed very good growth. Plant harvesting was done at 12 MST. The results of the final analysis of the cadmium (Cd) content in Impatiens balsamina planting medium soil was 0.1841 µg/g, while in plants it was 0.1306 µg/g. In the Mirabilis jalapa planting medium was 0.2061 μg/g, while in plants it was 0.1694 μg/g. The result of the analysis of biomass on flowering Impatiens balsamina L. and Mirabilis jalapa L. were 13.09% and 27.84%, metal removal was 34.73% and 38.88% and cadmium absorption efficiency was 24.64% dan 31.96%. The This shows that Impatiens balsamina and Mirabilis jalapa are able to accumulate the heavy metal cadmium in polluted soil.